The safety professional in the UK: Development of a key player in occupational health and safety. (October 2019) - Hale, Andrew; Booth, Richard
Highlights: UK history of safety professionals. Parallel development of inspectors and industry professionals. Generalist vs. specialist. Advisor vs. enforcer. Consequences for education and training. Abstract: The appointment of people working full time as advisers or enforcers for the prevention of work accidents and occupational diseases can be traced back in the UK (United Kingdom) to the factory inspectors in the early 19th Century. From the early 20th Century companies started to employ their own occupational safety and health (OSH) staff to undertake preventive tasks and to monitor compliance with legislation and company rules and procedures. Both the inspectorate and the companies faced comparable policy decisions about the role, selection, education and training of these OSH staff, who, by the 1940s, were taking the first steps to becoming a profession in the field of working conditions. This paper presents a historical summary of the developments in the UK which determined the role and requirements for appointment, education, training and work of both these groups of budding professionals (inspectors and company OSH staff). It traces the steps which have characterised this process of professionalisation, summarising them using as framework the criteria for becoming a recognised profession as set out in the introduction to this special issue (Hale et al., this issue).